A comparative study on different burning method of sewage sludge ash in mortar brick with eggshell powder as additive - Doh, Shu Ing; Muhammad Aizat, Azed; Chin, Siew Choo (American Institute of Physics Inc., 2017)
Population growth that increasing every year has led to the increasing number of waste generated annually. Sewage sludge and eggshell waste production that also increasing every year is the major concerns in this research. The high content of heavy metals in sewage sludge was recorded harmful to environment if it is not dumped in proper way at the landfill area. In general, Cd, Pb and Zn represent the biggest concentrations of heavy metals in sewage sludge which can be source of pollution. Furthermore, the excessive disposal of eggshells to landfills may attract rats and worms due to the organic protein matrix that may pose health problem to the public. The demand on cement mortar brick nowadays has increased due to the good development of construction industries. This will lead to the increase of cement production. However, cement plant is one of the major contributors of carbon dioxide emission in the world. Hence, this research is helping in reducing the production of cement in helping to greener environment where sewage sludge will act as cement replacement material as the element contains in Sewage Sludge Ash (SSA) present the same elements as cement. The major components of SSA are SiO2, CaO, Al2O3, Fe2O3, Na2O, K2O, MgO and FeO. It is necessary to burn the sewage sludge to remove the heavy metal before it can be applied as cement replacement materials in mortar brick production. In this research, two different method of burning the sewage sludge producing Sewage Sludge Ash (SSA) will be tested. Methods used in this research to burn the sewage sludge are incineration method produced Incinerated Sewage Sludge Ash (ISSA) and also microwave method, produced Microwaved Sewage Sludge Ash (MSSA). Eggshell powder act as additive in this research due to its high content of calcium carbonate and has nearly same composition of limestone used in the production of cement. Different percentages of Eggshell Powder (ESP) (0%, 5%, 10%, 15%) and 10% fixed of MSSA and ISSA as optimum dosage partially replacing the cement used to test the brick mortar properties in term of compressive strength, flexural strength and also water absorption. Result shows that ISSA with 10% replacement of ESP is the most optimum brick with highest compressive strength and flexural strength compared to MSSA brick. While, MSSA brick with 10% of ESP shown the best result in water absorption. But, the water absorption rate for 10% ESP in ISSA still good as low in its range.